O Impacto dos Subsídios Tributários Federais na Desigualdade de Renda no Brasil - Charles Mathusalem Soares Evangelista; Carlos Enrique Carrasco-Gutierrez (Revista de Economia Mackenzie)
This study aims to evaluate the effect of federal per capita tax subsidies on reducing income inequality in Brazil during the period from 2006 to 2019. To achieve this, we analyzed the annual Gini index in various regions of the country, considering variables such as per capita Gross Domestic Product (GDP), the average years of schooling for the population over 25 years old, regional population density, legal and constitutional transfers from the Union to the States per capita, and federal per capita tax subsidies granted in various economic and social sectors. We used a methodological approach that employed a panel data model, incorporating both fixed and random effects, and conducted the Hausman test to validate our model choice. The results highlight a significant relationship between federal per capita tax subsidies and income inequality, emphasizing the substantial influence of these subsidies on the configuration of income distribution. Thus, this study contributes to a deeper understanding of the economic and social dynamics in Brazil, highlighting the role of federal per capita tax subsidies in shaping income inequality patterns over the analyzed period.